Clinical effectiveness and cost-effectiveness of a multifaceted podiatry intervention for falls prevention in older people: a multicentre cohort randomised controlled trial (the REducing Falls with ORthoses and a Multifaceted podiatry intervention trial) - Sarah Cockayne; Sara Rodgers; Lorraine Green; Caroline Fairhurst; Joy Adamson; Arabella Scantlebury; Belen Corbacho; Catherine E Hewitt; Kate Hicks; Robin Hull; Anne-Maree Keenan; Sarah E Lamb; et al. (Health Technology Assessment, 2017)
Background: Falls are a serious cause of morbidity and cost to individuals and society. Evidence suggests that foot problems and inappropriate footwear may increase the risk of falling. Podiatric interventions could help reduce falls; however, there is limited evidence regarding their clinical effectiveness and cost-effectiveness. Objectives: To determine the clinical effectiveness and cost-effectiveness of a multifaceted podiatry intervention for preventing falls in community-dwelling older people at risk of falling, relative to usual care. Design: A pragmatic, multicentred, cohort randomised controlled trial with an economic evaluation and qualitative study. Setting: Nine NHS trusts in the UK and one site in Ireland. Participants: In total, 1010 participants aged ≥ 65 years were randomised (intervention, n = 493; usual care, n = 517) via a secure, remote service. Blinding was not possible. Interventions: All participants received a falls prevention leaflet and routine care from their podiatrist and general practitioner. The intervention also consisted of footwear advice, footwear provision if required, foot orthoses and foot- and ankle-strengthening exercises. Main outcome measures: The primary outcome was the incidence rate of falls per participant in the 12 months following randomisation. The secondary outcomes included the proportion of fallers and multiple fallers, time to first fall, fear of falling, fracture rate, health-related quality of life (HRQoL) and cost-effectiveness. Results: The primary analysis consisted of 484 (98.2%) intervention and 507 (98.1%) usual-care participants. There was a non-statistically significant reduction in the incidence rate of falls in the intervention group [adjusted incidence rate ratio 0.88, 95% confidence interval (CI) 0.73 to 1.05; p = 0.16]. The proportion of participants experiencing a fall was lower (50% vs. 55%, adjusted odds ratio 0.78, 95% CI 0.60 to 1.00; p = 0.05). No differences were observed in key secondary outcomes. No serious, unexpected and related adverse events were reported. The intervention costs £252.17 more per participant (95% CI –£69.48 to £589.38) than usual care, was marginally more beneficial in terms of HRQoL measured via the EuroQoL-5 Dimensions [mean quality-adjusted life-year (QALY) difference 0.0129, 95% CI –0.0050 to 0.0314 QALYs] and had a 65% probability of being cost-effective at the National Institute for Health and Care Excellence threshold of £30,000 per QALY gained. The intervention was generally acceptable to podiatrists and trial participants. Limitations: Owing to the difficulty in calculating a sample size for a count outcome, the sample size was based on detecting a difference in the proportion of participants experiencing at least one fall, and not the primary outcome. We are therefore unable to confirm if the trial was sufficiently powered for the primary outcome. The findings are not generalisable to patients who are not receiving podiatry care. Conclusions: The intervention was safe and potentially effective. Although the primary outcome measure did not reach significance, a lower fall rate was observed in the intervention group. The reduction in the proportion of older adults who experienced a fall was of borderline statistical significance. The economic evaluation suggests that the intervention could be cost-effective. Future work: Further research could examine whether or not the intervention could be delivered in group sessions, by physiotherapists, or in high-risk patients. Trial registration: Current Controlled Trials ISRCTN68240461. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 21, No. 24. See the NIHR Journals Library website for further project information.